Теоретико-методологічні засади саморозвитку регіону як потенціалу сталого розвитку - Гріневська, С.М. (Економіка промисловості, 2013)
Обґрунтовано теоретичні засади процесів саморозвитку регіону у взаємозв’язку із процесами підвищення рівня життя. Визначено методологічні підходи до дослідження проблем рівня та якості життя на принципах саморозвитку регіону як складових соціального потенціалу сталого розвитку. Запропоновано визначення понять: сталий розвиток, соціальний потенціал, рівень та якість життя населення, саморозвиток регіону, – у їх теоретичному взаємозв’язку. Розглянуто практики переходу економіки регіону до сталого розвитку на принципах саморозвитку, у їх взаємозалежності із процесами підвищення рівня та якості життя для визначення напрямів удосконалення державної регіональної політики.
Ключові слова: теорія та методологія процесів саморозвитку, державне регулювання, саморозвиток регіону, сталий розвиток, рівень та якість життя населення, соціальний потенціал. Обоснованы теоретические основы процессов саморазвития региона во взаимосвязи с процессами повышения уровня жизни. Определены методологические подходы относительно исследования проблем уровня и качества жизни на принципах саморазвития региона как составляющей социального потенциала устойчивого развития. Предложено определение понятий: устойчивое развитие, социальный потенциал, уровень и качество жизни населения, саморазвитие региона, – в их теоретической взаимосвязи. Рассмотрены практики перехода экономики региона к устойчивому развитию на принципах саморазвития в их взаимозависимости с процессами повышения уровня и качества жизни для определения направлений усовершенствования государственной региональной политики.
Ключевые слова: теория и методология процессов саморазвития, государственное регулирование, саморазвитие региона, устойчивое развитие, уровень и качество жизни населения, социальный потенциал. The questions of the socio-economic measures of stable development in the region’s self-develop¬ment context are considered. The strategic directions of region’s self-development for providingstable development are proposed.
In socio-economic aspect the stable development of a region means the increasing of level and quality of life that implies overcoming unfavorable social, economic and ecological tendencies, preserving the possibility of a region to provide balanced development, self-regulation, self-improving with the usage of inner and outer loan resources to satisfy needs of people within a region.
The self-development of a region can be defined as an ability of region’s economy in certain conditions to provide balanced development, forced increase in gross regional product for personal finances and creation of competitive atmosphere in a region directed to socio-economic development and corresponding to the increase in the quality of life, including optimal consolidation of providing regional self-regulation and state regulation of territorial development.
By the level of regional self-development a definite state of a region is meant and it is conditioned by the totality of inner regularity of self- development that is reflected in the indicator of quantity. The indicators of socio-economic development that characterize region’s self-development potential are proposed, namely: GRP in actual prices as a generalizing socio-economic indicator of regional self-development; the volume of industrial products sold; the quantity of people engaged in the sphere of economy; the content of building works executed; the volume of servicessold; the investment in fixed capital; industrial enterprises that implement innovations among other enterprises; export of products and services; main means; real income per capita; expenses of population per capita; average monthly salaries and wages; saving – deposits of housekeeping in national and foreign currency; subsidies. Optimal relation of these indicators of self-development to GRP will make for the economic development of a region.
Keywords: theory and practice of self-deve-lop¬ment processes, government regulation, region’s self-development, stable development, level and quality of life, social potential.